Beacons of modern learning: Diaspora-funded schools in the China-Australia corridor. (June 2020) - Cheng, Christopher
In the early 20th century, modern school curricula and new-style schools mushroomed in the Chinese remittance landscape of southern China. Breaking away from the two-and-a-half millennia of Confucian tradition, their creation marked a pivotal point of departure between the nation's past and future. Since overseas migration and modern education both provide a fruitful context for the circulation of new objects and a cross-fertilization of ideas, new schools serve as barometers of social-material change. Research in the present-day cities of Zhongshan and Zhuhai (formerly Heung San County) suggests that diaspora-funded schools were beacons of modern learning within the China–Australia corridor. Both their physical structures and material manifestations invited a new engagement with the modern world.